2020
DOI: 10.3390/jcm9093054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Amino Acid Mix on the Secretion of Gastrointestinal Peptides, Glucometabolic Homeostasis, and Appetite in Obese Adolescents Administered with a Fixed-Dose or ad Libitum Meal

Abstract: Proteins have been demonstrated to reduce food intake in animals and humans via peripheral and central mechanisms. Supplementation of a dietetic regimen with single or mixed amino acids might represent an approach to improve the effectiveness of any body weight reduction program in obese subjects. The aim of the present study was to evaluate the effects of an amino acid mix (L-arginine + L-leucine + L-glutamine + L-tryptophan) on the secretion of some gastrointestinal peptides (i.e., ghrelin and glucagon-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…More specifically, studies in human beings have shown positive results following the administration of L-arginine. This amino acid appears to be capable of evoking an anorexigenic response by increasing postprandial responses of the anorectic gut peptides Glucagon-like-peptide-1 (GLP-1) and Peptide tyrosine tyrosine (PYY) in subjects with normal weight or obesity [15,16]. L-arginine supplementation also appears to improve anthropometric parameters (body weight, waist circumference), blood pressure levels and certain blood biochemical indices associated with cardiovascular disease prevention [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, studies in human beings have shown positive results following the administration of L-arginine. This amino acid appears to be capable of evoking an anorexigenic response by increasing postprandial responses of the anorectic gut peptides Glucagon-like-peptide-1 (GLP-1) and Peptide tyrosine tyrosine (PYY) in subjects with normal weight or obesity [15,16]. L-arginine supplementation also appears to improve anthropometric parameters (body weight, waist circumference), blood pressure levels and certain blood biochemical indices associated with cardiovascular disease prevention [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In obese participants, L-Trp (1.56 g orally) increased GLP-1 secretion and reduced gastric emptying; however, L-Leucine did not stimulate GLP-1 secretion [52]. Furthermore, in humans, oral administration of an amino acid mixture containing 3 g L-arginine, 3 g L-Trp, 6 g L-glutamine, and 6 g L-leucine, modestly reduced appetite and increased GLP-1 levels in obese adolescents [53]. In healthy, lean men, whey protein containing all amino acids including L-Trp increased the GLP-1 and insulin [54].…”
Section: Discussionmentioning
confidence: 94%
“…Amino acids deriving from the digestion of proteins present in our diet may be chemo-sensed, not only at the peripheral level by enteroendocrine cells but also at the central level by hypothalamic neurons; single or mixed amino acids can influence the secretion of some gastrointestinal peptides and, consequentially, regulate appetite. It was in such a context that a study was performed by Rigamonti et al (2020) to evaluate the effects of an amino acid mix (L-arginine + L-leucine + L-glutamine + L-tryptophan) on the secretion of some gastrointestinal peptides (i.e., ghrelin and glucagon-like peptide type-1, GLP-1), glucometabolic homeostasis (i.e., glucose, insulin, and glucagon), and appetite (hunger/satiety scored by a visual analog scale, VAS) in obese adolescents [ 55 ]. Indeed, L-arginine, L-leucine, L-glutamine, and L-tryptophan, administered to obese adolescents with a fixed-dose meal, were capable of evoking an anorexigenic response.…”
Section: Discussionmentioning
confidence: 99%